PENERAPAN ASUHAN KEBIDANAN BERKELANJUTAN PADA NY. W, NY. N, NY. F DI PMB IMELDA, S.ST TULANG BAWANG TAHUN 2023 - Yesika Tusiana; Supriyati; Yetty Dwi Fara (LPPM STIKes Mitra Adiguna, 2023)
Even though pregnancy, childbirth and menopause are natural processes, there is still a chance that something could go wrong with the woman or her baby. Warm breast compresses as a postpartum intervention aim to relieve pain, accelerate healing, improve blood flow, and relax the client by breaking down fibrous tissue and relaxing muscles. The purpose of this study was to find out whether Mrs.W and Mrs.F at PMB Imelda, S.ST, Tulang Bawang Regency in 2023 experienced a decrease in breast swelling. Case studies and descriptive methods based on interviews and archival research are viable options for gathering information for research. The research was conducted in 2023 at PMB Imelda, S.ST, Tulang Bawang Regency, from January to April. Pregnant women in the PMB Imelda S.ST, Tulang Bawang Regency in 2023 with a gestational age > 36 weeks were the subjects in the cases taken. The results showed that postpartum women whose breasts were swollen experienced a reduction in swelling after being given warm compresses. Warm compresses have been shown to reduce pain by constricting blood vessels, dulling the sensation of pain, and dampening the activity of nerve endings associated with muscles. Suggestions for health workers can boost the standard of midwifery care and ensure that patients get continuity of care.